Autonomous soil analysis by the Mars Micro‐beam Raman Spectrometer (MMRS) on‐board a rover in the Atacama Desert: a terrestrial test for planetary exploration. (9th February 2015) - Wei, Jie; Wang, Alian; Lambert, James L.; Wettergreen, David; Cabrol, Nathalie; Warren‐Rhodes, Kimberley; Zacny, Kris; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> Laser Raman spectroscopy (LRS) has been proposed for in situ characterization of molecular species in planetary surface exploration, and three laser Raman spectrometers are included in the science payloads of two under‐development missions to Mars (ESA‐ExoMars2018 and NASA‐Mars2020). We report the first rover test of a laser Raman spectrometer developed for flight, the Mars Micro‐beam Raman Spectrometer (MMRS) in the Atacama Desert (Chile). The MMRS was integrated on the Zoë rover and analyzed subsurface samples brought up by a 1 m drill and delivered by a carousel. The MMRS demonstrated robust performance over 50‐km traverse on rugged terrains. From MMRS data, igneous minerals, carbonates, sulfates and carbonaceous materials were unambiguously identified. Quantified distributions of major minerals and carbonaceous materials are extracted from MMRS results, which can be used to imply the regional geological evolution, and potential bioactivities. MMRS in the field performed as well as an LRS laboratory instrument when MMRS was focused satisfactorily. The discovery of stable γ‐anhydrite, in large quantity (20% in a sample), in the Atacama soils raises an important question of its stability in the field in a natural environment that is worth further laboratory experimental investigation. Copyright © 2015 John Wiley & Sons, Ltd.